Religious Guidance at SMC Samarinda Hospital: Bimbingan Kerohanian di Rumah Sakit SMC - Mursalim; Imanuddin; Isna Maulida Mandini; Misbahul Ramadhani; Khusnul Khatimah (Journal of Empowerment and Community Service (JECSR), 2023)
Spiritual guidance at SMC Samarinda Hospital is a community service initiative aimed at providing spiritual support to patients and their families. This research was chosen due to the importance of supporting holistic health in medical practice. The service method involves the formation of a trained spiritual guidance team that is sensitive to the spiritual needs of patients from various backgrounds. The results indicate that spiritual guidance provides significant emotional and spiritual support to patients and has a positive impact on their healing process. These findings reaffirm the importance of integrating spiritual aspects into modern healthcare. Spiritual guidance at SMC Samarinda Hospital is not just about providing physical treatment, but also about healing the soul and mind